The Doctrine of the Jews and Their Philosophy in The Door of Divinities, Prophecies and Audios - Tofiq, Dheyih H.; Abdullah, Zana N. (Humanities Journal of University of Zakho, 2019)
There is no doubt that all consignments of God sent to the slaves confirms that Adam, the first human being created by God, the Prophet carrying a message commensurate with the time and place conditions, when it came down to the ground, because the wisdom of God and his righteousness spend that carries a divine message, but it is impossible to reason and quoting, that God leaves the slaves without religion regulates matters of life and the afterlife. It was all consignments of Allah to his prophets -alehm Salam include centrist and moderate, and order in the content moderation and standardization in terms of faith; therefore Tafrgna to conduct a search includes the doctrine of Abrahamic faiths, and that no one touches by her side lumpy and uncover topics Streptococcus moderation that have not After writing about this depth and meditation, also We searched for common points between each of them both, as well as reference to the excessiveness, without bias to this and that.